KOMPETENSI PRAGMATIK ANAK USIA 3-5 TAHUN MELALUI MEDIA VIDEO BLOGGER: KAJIAN PSIKOPRAGMATIK - Rizal, Muhammad (Translation and Linguistics (Transling), 2022)
This study shows the fact that children have the ability to produce complete speech at the age of under 6 years. The development of pragmatic competence is seen using the theory of Horn and Ward (2006), which consists of eight components. The research subjects were siblings ranging in age from 3 to 5 years who were well known (viral) through a video of which they were proficient in reciting selawat. The data taken is in the form of video recordings of the two children with the title "Q&A Game" with their father and uncle which were posted around May and July 2019. The results show that Qeisya's pragmatic competence from the age of 3 - 4 years is good, except for the Taking Turns aspect and Convention and Contrast (C&C) which is still failing, while Aisywa's pragmatic competence from the age of 4-5 years is good in all aspects. The politeness aspect has not been found in the two subjects studied.